DOES AQUATIC EXERCISE IMPROVE QUALITY OF LIFE IN OBESE LOW-BACK PAIN POPULATION? (International Journal of Physiotherapy, 2019)
Background: Low-back pain is one of the most common reasons for work stress, poor health, sickness, and reducing the quality of life. While obesity is a growing public health concern, it was proved that obesity is a risk factor for low back pain. Whereas obese low-back pain people cannot avoid weight load on the spine in any exercise, but they can easily carry out the exercise in water. This study aimed to know the effect of aquatic exercise on quality of life among obese low-back pain people.Methods: A total of 39 women with BMI≥27 kg.m-2 who had non-specific chronic low-back pain were purposively selected for this study. They randomly assigned in two groups; exercising (N=19, 37.85±5.83 years with 32.97±4.84kg.m-2) and control group (N=20, 40.8±5.25 years with 31.87±4.79 kg.m-2). The exercising group carried out the aquatic exercise, twice per week, 60 minutes per session, for 12 weeks. Quality of life was measured using the SF-36v2 questionnaire with eight domains; physical functioning, role-physical, bodily pain, general health, vitality, social functioning, role-emotional, and mental health.Results: The findings showed a significant (p≤0.001) improvement in the quality of life in the exercising group after 12 weeks. The significant improvement was found on seven domains of the SF-36v2 in the exercising group after the aquatic exercise intervention program while there was no significant effect on mental health (p=0.051). In the control group, a negative change in mean difference (-3.02) was observed in the mental health domain, while it was changed (15.32) for the exercising group. There was no significant change in BMI in both groups, also.Conclusion: In conclusion, a 12-week aquatic exercise is an appropriate intervention program to improve the overall quality of life among obese women who are suffering from non-significant chronic low- back pain.